Predictive Value of Cord Blood Concentrations of Selected Hepatic Enzymes in Hypoxic-Ischaemic Encephalopathy and Related Mortality - Ariyibi, SO; Ojuawo, AI; Adesiyun, OO; Adebara, OV; Ogunwale, KA; Ojuawo, AO; Ray, EO; Sanusi, IA (Annals of Health Research (Onabanjo University Teaching Hospital), 2024)
Background: Hypoxic-ischaemic encephalopathy remains a major threat to newborn survival, especially in developing countries. Objectives: To evaluate the predictability of some hepatic biomarkers for hypoxic-ischaemic encephalopathy (HIE) and mortality post-asphyxia event. Methods: This case-control cross-sectional study was carried out among 70 asphyxiated newborns and 70 healthy newborns. Cord blood sample was obtained at delivery for analysis of serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) and lactate dehydrogenase (LDH). Enzyme assay was done using spectrophotometric method. The Receiver Operating Characteristics (ROC) curve was used to determine the sensitivity and specificity of the enzymes, and the positive and negative predictive values were extrapolated from these. Results: Out of the 70 asphyxiated babies, 48 (68.6%) had HIE and five (7.1%) died. The area under curve (AUC) values for AST, ALT and LDH levels in the ROC curve were all statistically significant as predictors of HIE, best for AST (AUC = 0.873, p < 0.001). A cut-off level of ≥71.5U/L for cord blood AST was the best predictor of HIE with a sensitivity, specificity and positive predictive values of 64.6%, 95.5% and 96.9% respectively. Meanwhile, the AUC value for predicting mortality was only significant for AST (AUC = 0.783, p = 0.036). Conclusion: Hepatic enzymes, especially AST, can be used as early diagnostic biomarkers of perinatal asphyxia and can predict HIE. They are however less reliable as predictors of mortality.